A Combination of Deworming and Prime-Boost Vaccination Regimen Restores Efficacy of Vaccination Against Influenza in Helminth-Infected Mice - Stetter, Nadine; Hartmann, Wiebke; Brunn, Marie-Luise; Stanelle-Bertram, Stephanie; Gabriel, Gülsah; Breloer, Minka (Frontiers in Immunology, 2021)
Helminths still infect a quarter of the human population. They manage to establish chronic infections by downmodulating the immune system of their hosts. Consequently, the immune response of helminth-infected individuals to vaccinations may be impaired as well. Here we study the impact of helminth-induced immunomodulation on vaccination efficacy in the mouse system. We have previously shown that an underlying Litomosoides sigmodontis infection reduced the antibody (Ab) response to anti-influenza vaccination in the context of a systemic expansion of type 1 regulatory T cells (Tr1). Most important, vaccine-induced protection from a challenge infection with the 2009 pandemic H1N1 influenza A virus (2009 pH1N1) was impaired in vaccinated, L. sigmodontis-infected mice. Here, we aim at the restoration of vaccination efficacy by drug-induced deworming. Treatment of mice with Flubendazole (FBZ) resulted in elimination of viable L. sigmodontis parasites in the thoracic cavity after two weeks. Simultaneous FBZ-treatment and vaccination did not restore Ab responses or protection in L. sigmodontis-infected mice. Likewise, FBZ-treatment two weeks prior to vaccination did not significantly elevate the influenza-specific Ig response and did not protect mice from a challenge infection with 2009 pH1N1. Analysis of the regulatory T cell compartment revealed that L. sigmodontis-infected and FBZ-treated mice still displayed expanded Tr1 cell populations that may contribute to the sustained suppression of vaccination responses in successfully dewormed mice. To outcompete this sustained immunomodulation in formerly helminth-infected mice, we finally combined the drug-induced deworming with an improved vaccination regimen. Two injections with the non-adjuvanted anti-influenza vaccine Begripal conferred 60% protection while MF59-adjuvanted Fluad conferred 100% protection from a 2009 pH1N1 infection in FBZ-treated, formerly L. sigmodontis-infected mice. Of note, applying this improved prime-boost regimen did not restore protection in untreated L. sigmodontis-infected mice. In summary our findings highlight the risk of failed vaccinations due to helminth infection.